Використання процеса охолодження у зерносховищі в період зберігання зернової продукції - Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Kiurchev, Serhii; Паламарчук, Ігор Павлович; Паламарчук, Игорь Павлович; Palamarchuk, Ihor; Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна; Verkholantseva, Valentyna; Кюрчева, Людмила Миколаївна; Кюрчева, Людмила Николаевна; Kiurcheva, Liudmyla (ТДАТУ, 2020)
UK: Стаття присвячена розгляду проблеми зберігання зернової продукції із застосуванням нового обладнання для зерносховища. Запропонований імпульсний пневмодинамічний барботер забезпечує активне зворушення часток сипкого зернового середовища як у повздовжньому, так і в поперечному напрямах за рахунок генерації зустрічних хвильових потоків охолодженого повітря без використання механічних робочих органів інтенсифікації процесу за достатньо простого та надійного конструкційного виконання. Дана принципова схема сховища для зберігання сільськогосподарської продукції, яка реалізує ідею комплексної технологічної обробки зернової маси за рахунок ефективного розподілу охолодженого потоку повітря, що проходить крізь сировину, регулюючи його газовий склад у міжзернових проміжках, температуру, вологість та інтенсивність фізико-мікробіологічних процесів в оброблюваній продукції. EN: The article is devoted to the problem of storage of grain products with the use of new equipment for granaries. The proposed pulsed pneumodynamic bubbler provides active movement of bulk grain particles in both longitudinal and transverse directions by generating counter-wave flows of cooled air without the use of mechanical working bodies to intensify the process with a fairly simple and reliable design. The basic scheme of storage for storage of agricultural products is given, which realizes the idea of complex technological processing of grain mass due to effective distribution of the cooled stream of air passing through raw materials, regulating its gas composition in intergrain intervals, temperature, humidity and intensity of physical and microbiological processes. The support surface of the pallet is made of metal, which is lined with sheet metal around the perimeter to increase the load-bearing capacity of the structure and the possibility of securing the pallet system on special support posts. Grain products are supposed to be stored not on the floor in bulk, but at a certain distance from it to prevent unwanted moisture in the products. At the same time placement of grain is carried out in special pallets on the end walls of which the developed pneumopulse generators or bubblers are mounted opposite to each other. The products are located some distance from the floor, the distribution of air flows to the flowing medium is effected through a manifold that connects separately to each pallet, which are parallel to each other for ease of access and ability to form a standing wave. As a result of the interaction of counterpropagating pneumatic waves and their superposition, standing waves are formed, which transfer kinetic energy both in the longitudinal and in the flows, which in turn touch the grain mass. Under such conditions of storage of the grain mass, the caking and activation of undesirable microbiological processes are practically excluded. RU: Статья посвящена рассмотрению проблемы хранения зерновой продукции с применением нового оборудования для зернохранилища. Предложенный импульсный пневмодинамичний барботер обеспечивает активное волнения частиц сыпучего зерновой среды как в продольном, так и в поперечном направлениях за счет генерации встречных волновых потоков охлажденного воздуха без использования механических рабочих органов интенсификации процесса за достаточно простого и надежного конструкционного исполнения. Данная принципиальная схема хранилища для хранения сельскохозяйственной продукции, реализует идею комплексной технологической обработки зерновой массы за счет эффективного распределения охлажденного потока воздуха, проходящего через сырье, регулируя его газовый состав в межзернового промежутках, температуру, влажность и интенсивность физикомикробиологических процессов в обрабатываемой продукции .
Использование процесса охлаждения в зернохранилище в период хранения зерновой продукции
Use of the cooling process in the grain storage during the period of storage of grain products
Keywords: зберігання; зерно; барботер; зерносховище; процес; зворушення; повітря; хвиля; хранение; зернохранилище; процесс; волнения; storage; grain; bubbler; granary; process; touch; air; wave